O trabalho em equipe no contexto da intepretação entre língua portuguesa e libras: uma experiência na esfera comunitária - Pedrosa, Luiza (Universidade Federal de São Carlos, 2019)
This paper presents and discusses the performance of a team of translators / interpreters of Libras (TILS) in a course offered to the community and which aims to bring information to groups of women through training on their rights. The course is offered in a city in the interior of the state of São Paulo and is held weekly, involving different themes that are interconnected to the daily life of the female community (such as, for example, women's health, protection against domestic violence and legal guidance). When the meeting became accessible to deaf women, the work of the TILS team came into question, which began to operate in a context that we characterize here as a community. Therefore, with this qualitative research, it is intended to present the organization of the TILS team active in the weekly meetings of this course, presenting and questioning the need for prior and subsequent organization of the interpretation team considered more appropriate for the work to be developed, investigating the strategies adopted by this team.
Teamwork in the context of interpretation between portuguese language and libras: an experience in the community sphere
Keywords: Interpretação Libras/Língua Portuguesa; Intérprete de apoio; Trabalho em equipe; Esfera comunitária; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS